Polarimetric radar signatures of precipitation at S- and C-bands - Golestani, Y., author; Hubbert, J., author; Meischner, P., author; Chandrasekar, V., author; Bringi, V. N., author; IEE, publisher (Colorado State University. Libraries, 1991)
Polarimetric radar measurements in precipitation at S- and C-band frequencies are considered. Time series data were obtained from three advanced radars: the National Center for Atmospheric Research (NCAR) CP-2 radar, the National Severe Storms Laboratory's (NSSL) Cimarron radar, and the C-band Poldirad radar operated by the German Aerospace Research Establishment (DLR). Measurements of radar reflectivity, differential reflectivity ZDR, differential propagation phase ϕDP, and the crosscorrelation between horizontal and vertical polarised waves are derived from time series data in rain, rain mixed with ice, and in the stratiform ice phase of convective storms. Raindrops are modelled as oblate in shape with a gamma form for their size distribution. The gamma parameters (N0, D0>, m) are varied over an entire range encompassing a wide variety of rainfall types. The radar rain measurements are shown to be in good general agreement with the model rain simulations. By combining ZDR and ϕDP it is possible to identify regions of mixed particle types, e.g. raindrops and hail, or ice crystals and snowflakes. The differential phase upon backscatter may be identified by examining the range profile of ϕDP, giving additional clues as to the type and size of particles responsible for the backscatter.
Keywords: radar; polarimetry; propagation